Role of UFMylation in tumorigenesis and cancer immunotherapy - Ding, Li-juan; Jiang, Xin; Li, Te; Wang, Shudong (Frontiers in Immunology, 2024)
Protein post-translational modifications (PTMs) represent a crucial aspect of cellular regulation, occurring after protein synthesis from mRNA. These modifications, which include phosphorylation, ubiquitination, acetylation, methylation, glycosylation, Sumoylation, and palmitoylation, play pivotal roles in modulating protein function. PTMs influence protein localization, stability, and interactions, thereby orchestrating a variety of cellular processes in response to internal and external stimuli. Dysregulation of PTMs is linked to a spectrum of diseases, such as cancer, inflammatory diseases, and neurodegenerative disorders. UFMylation, a type of PTMs, has recently gained prominence for its regulatory role in numerous cellular processes, including protein stability, response to cellular stress, and key signaling pathways influencing cellular functions. This review highlights the crucial function of UFMylation in the development and progression of tumors, underscoring its potential as a therapeutic target. Moreover, we discuss the pivotal role of UFMylation in tumorigenesis and malignant progression, and explore its impact on cancer immunotherapy. The article aims to provide a comprehensive overview of biological functions of UFMylation and propose how targeting UFMylation could enhance the effectiveness of cancer immunotherapy strategies.